Perbedaan Model Pembelajaran Creative Problem Solving dan Ideal Problem Solving Berorientasi Experiential Learning Ditinjau Dari Hasil Belajar dan Motivasi Mahasiswa - Imron, Ilmawati Fahmi (Efektor, 2025)
The problem in this study Lecturers apply lecture and assignment models, so that students do not understand the material on humans and their environment. The impact is that student motivation and learning outcomes decrease. To overcome this problem, Creative Problem Solving and IDEAL Problem Solving are applied which are oriented towards Experiential Learning. The research subjects are 1st semester PGSD students. The sample uses a random sampling technique of 2 classes. This study uses an Experimental method with a two-way ANOVA analysis technique with a 2x2 path. Learning outcome data uses tests and learning motivation data uses questionnaires with a Likert scale. The data analysis technique used for test data is SPSS, a significance level of 5% (0.05) Meanwhile, learning motivation data uses a questionnaire with a Likert scale with data interpretation 13-20: high motivation category and 0-12: low motivation category. The results of the study were 1) P-value model 0.842 > 0.05, then Ha was accepted, meaning that there was a difference in learning outcomes of students who received Creative Problem Solving treatment oriented to Experiential Learning and IDEAL Problem Solving oriented to Experiential Learning, 2) P-value motivation 0.001 <0.05, then Ha was rejected, meaning that there was no difference in motivation between students who were given lectures on the Creative Problem Solving model oriented to Experiential Learning and IDEAL Problem Solving oriented to Experiential Learning, 3) P-value interaction model with motivation 0.017 <0.05, then Ha was rejected, meaning that there was no interaction between the Creative Problem Solving model oriented to Experiential Learning and IDEAL Problem Solving oriented to Experiential Learning with student learning motivation.